Les activités de gestion d’alerte épidémiologique : les transformations induites par l’utilisation d’un système de surveillance en temps réel - Charlotte Gaudin; Natalie Bonnardel; Lilianne Pellegrin; Hervé Chaudet (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper presents a study that investigated the management of epidemiological alerts. Alert management is a complex, distributed medical activity. It can be compared to the largest category of dynamic environment management. Two activities were examined. First, we analyzed traditional alert management activity with the MAD method (observations and interviews). Second, we analyzed and characterized alert management activities when supported by the computerized ASTER system (Alerte et Surveillance en TEmps Réel, alert and monitoring in real time). The second analysis was conducted with EORCA method, which is used to describe collective and complex activities. The results highlight various modifications to both the cognitive activity and team activities which were due to the use of the ASTER system.